1999
DOI: 10.1007/s00585-999-0066-9
|View full text |Cite
|
Sign up to set email alerts
|

Auroral pulsations and accompanying VLF emissions

Abstract: Abstract. Results of simultaneous TV observations of pulsating auroral patches and ELF-VLF-emissions in the morning sector carried out in SodankylaÈ (Finland) on February 15, 1991 are presented. Auroral pulsating activity was typical having pulsating patches with characteristic periods of about 7 s. Narrow-band hiss emissions and chorus elements at intervals of 0.3±0.4 s formed the main ELF-VLF activity in the frequency range 1.0±2.5 kHz at the same time. The analysis of auroral images with time resolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 40 publications
(51 reference statements)
7
32
2
Order By: Relevance
“…Each dynamic spectrum shows successive rising-tone elements with an element duration and spacing of approximately 0.1-0.3 s, a duration of grouped elements of 2-3 s, and a spacing of each group of 20-30 s. These features observed in the chorus wave spectra are consistent with the values for pulsating auroral patches [Yamamoto, 1988;Samara and Michell, 2010]. Similar results from ground-based observations suggest that a wave-particle interaction may be the generating mechanism of pulsating aurora [Tsuruda et al, 1981;Hansen and Scourfield, 1990;Tagirov et al, 1999]. The first step toward estimating the location of the source region is to determine which auroral patch is spatially related to the observed chorus waves.…”
Section: Natural Vlf Waves and Optical Observationssupporting
confidence: 81%
“…Each dynamic spectrum shows successive rising-tone elements with an element duration and spacing of approximately 0.1-0.3 s, a duration of grouped elements of 2-3 s, and a spacing of each group of 20-30 s. These features observed in the chorus wave spectra are consistent with the values for pulsating auroral patches [Yamamoto, 1988;Samara and Michell, 2010]. Similar results from ground-based observations suggest that a wave-particle interaction may be the generating mechanism of pulsating aurora [Tsuruda et al, 1981;Hansen and Scourfield, 1990;Tagirov et al, 1999]. The first step toward estimating the location of the source region is to determine which auroral patch is spatially related to the observed chorus waves.…”
Section: Natural Vlf Waves and Optical Observationssupporting
confidence: 81%
“…Deviations from other magnetic field models were investigated in our separate study [Nishimura et al, 2011]. The existence of multiple cores and the expanding and propagating features of patches are similar to the events reported by Tagirov et al [1999].…”
Section: Correlation Between Pulsating Aurora and Lower-band Chorussupporting
confidence: 64%
“…Figure 6 magnifies the interval following the dipolarization, and relates the earthward bulk flow and the flux pileup to the electron temperature anisotropy, as discussed later in detail. The periodicity of the bursts is about 0.2 to 0.4 s, as observed previously for chorus waves (Helliwell, 1965;Tagirov et al, 1999). The fourth panel is the SCM wave burst interval starting at about 05:29:36.225 that falls between the dashed lines in the panel above.…”
Section: Discussionsupporting
confidence: 73%
“…A recent Time History of Events and Macroscale Interactions during Substorms (THEMIS) study of fast bursty bulk flows at L = 9 reveals that quasi-parallel whistler waves produced in the fast flows associated with dipolarization fronts are able to resonate with and scatter 2-26 keV electrons (Zhima et al, 2015). Tagirov et al (1999) observe VLF chorus emissions in concert with auroral pulsations in the morning sector during substorm activity, based on ground-based VLF recordings and optical measurements in Sodankylä, Finland. This is in contrast to other studies that found the waves were produced within the magnetic depressions Tsurutani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%